2005
DOI: 10.1029/2004ja010848
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal structure of the equatorial anomaly in the nighttime ionosphere observed by IMAGE/FUV

Abstract: [1] The Far Ultraviolet Imager (FUV) on board the IMAGE satellite provides an instantaneous global view of the OI 135.6-nm nightglow with 2 min time resolution. Because the OI 135.6-nm emission from the nighttime ionosphere is determined by the line-of-sight integrated plasma density, the nightglow images are useful for studying the nighttime low-latitude ionosphere globally. With the IMAGE/FUV 135.6-nm observations from March to June 2002, we have examined the global characteristics of the nighttime equatoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
307
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(332 citation statements)
references
References 39 publications
(46 reference statements)
23
307
1
1
Order By: Relevance
“…7, a large-scale longitudinal structure, which is similarly reported by many scientists (e.g. Sagawa et al, 2005;Immel et al, 2006;Lin et al, 2007;Kakinami et al, 2011), is clearly seen around the magnetic equator in the F3/C model. According to Kakinami et al (2011), the 4-peak structure of N e at 660 km observed with the DEMETER satellite is the most pronounced in September while a 3-peak structure appears in March and December.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…7, a large-scale longitudinal structure, which is similarly reported by many scientists (e.g. Sagawa et al, 2005;Immel et al, 2006;Lin et al, 2007;Kakinami et al, 2011), is clearly seen around the magnetic equator in the F3/C model. According to Kakinami et al (2011), the 4-peak structure of N e at 660 km observed with the DEMETER satellite is the most pronounced in September while a 3-peak structure appears in March and December.…”
Section: Resultssupporting
confidence: 60%
“…The International Reference Ionosphere (IRI) has been developed since 1978 (Rawer et al, 1978) and is established as the most standard and reliable ionospheric empirical model. Since a large amount of ionosonde data has been used, IRI derives a relatively accurate electron density (N e ) profile below the F 2 peak.…”
Section: Introductionmentioning
confidence: 99%
“…The phase of the SPW defines the longitude where the wave crest occurs. At low and equatorial latitudes the WN4/WN3 patterns of the ionospheric and thermospheric quantities and the related tidal components have been widely studied (Sagawa et al, 2005;Immel et al, 2006;England et al, 2006England et al, , 2010Lühr et al, 2008Lühr et al, , 2012Kil et al, 2007;Häusler and Lühr, 2009;Zhang et al, 2010;Xiong and Lühr, 2013;. These tides originate from the lower atmosphere and can propagate upward to the upper atmosphere, either by direct propagation or through the E region wind dynamo coupling mechanism (e.g.…”
Section: Y-l Zhou Et Al: Solar Activity Dependence Of Nonmigratingmentioning
confidence: 99%
“…A prominent four-peak longitudinal structure of the equatorial ionization anomaly (EIA) has been discovered by global satellite observations [e.g., Sagawa et al, 2005;England et al, 2006a;Immel et al, 2006;Lin et al, 2007]. In addition, according to modeling works, the longitudinal dependence of tropospheric convection has been shown to be an important source for the excitation of solar nonmigrating (non-Sun-synchronous) tides that propagate upward to the thermosphere, including the diurnal eastward-propagating tide with zonal wave number 3 (DE3), which has four peaks in the local-time fixed frame [e.g., Forbes, 2002, 2003;Miyoshi, 2006].…”
Section: Introductionmentioning
confidence: 99%